La nocturnité au quotidien chez les Indiens tseltal du Chiapas (Mexique) - Aurore Monod Becquelin; Marie Chosson (Ateliers d'Anthropologie)
This analysis invites us to scrutinise the Tseltal night from the perspective of its role as an agent of behaviours, thoughts, attitudes, and corporeal habits among these natives of the Mexican Highlands.As the home of sleep, night enables the dreamer to mix with supernatural beings, making accessible and visible a dynamic cosmos in which plants, animals, humans and nonhumans interact. However, certain traits that define this night extend beyond the nocturnal part of the nychthemeron in order to emerge on its diurnal side, what we call manifestations of nocturnity. The ontological displacement characteristic of nocturnity makes it possible to place a permanent fear in the unconscious that it will irrupt in people’s lives; this fertile subsoil is perceptible in everyday conversation, in repeated tales, in gestures, and in the avoidance behaviours that reveal it. Based on field data from two communities, Bachajón and Aguacatenango, broadened to other villages located in Los Altos, we show that while the dark component of the definition of the Tsteltal night is viewed as dangerous and likely to be fatal to humans, it is also seen as necessary. It is therefore indispensable to compromise oneself at the threshold of danger and, by dint of everyday efforts, repeated rituals and prayers, obtain the benefits necessary for life by communicating with beings born of that darkness.